Giving and receiving: A study of barriers and enablers in Asian philanthropy - SIDHU, Dalvin (Institutional Knowledge at Singapore Management University, 2020)
This report provides an insight into Asian philanthropy through engaging with philanthropic entities (PEs) in Greater China, India and Indonesia. Issues pertinent to this research include (1) challenges and opportunities for philanthropy in the region, (2) the interest and readiness of PEs to address common regional problems, (3) identifying support and platforms that would effectively help translate giving strategies into impact, (4) the interest and readiness of PEs to explore and engage in innovative ways, and (5) identifying the major areas in which these PEs are involved.